Bone marrow mesenchymal stem cells derived exosomal miRNAs can modulate diabetic bone-fat imbalance - Han, Fei; Wang, Chao; Cheng, Peng; Liu, Ting; Wang, Wei-Shan (Frontiers in Endocrinology, 2023)
Background: Diabetes mellitus is a chronic metabolic disease with systemic complications. Patient with diabetes have increased risks of bone fracture. Previous studies report that diabetes could affect bone metabolism, however, the underlying mechanism is still unclear. Methods: We isolated exosomes secreted by bone marrow mesenchymal stem cells of normal and diabetic mice and test their effects on osteogenesis and adipogenesis. Then we screened the differential microRNAs by high-throughput sequencing and explored the function of key microRNA in vitro and in vivo. Results: We find that lower bone mass and higher marrow fat accumulation, also called bone-fat imbalance, exists in diabetic mouse model. Exosomes secreted by normal bone marrow mesenchymal stem cells (BMSCs-Exos) enhanced osteogenesis and suppressed adipogenesis, while these effects were diminished in diabetic BMSCs-Exos. miR-221, as one of the highly expressed miRNAs within diabetic BMSCs-Exos, showed abilities of suppressing osteogenesis and promoting adipogenesis both in vitro and in vivo. Elevation of miR-221 level in normal BMSCs-Exos impairs the ability of regulating osteogenesis and adipogenesis. Intriguingly, using the aptamer delivery system, delivery normal BMSCs-Exos specifically to BMSCs increased bone mass, reduced marrow fat accumulation, and promoted bone regeneration in diabetic mice. Conclusion: We demonstrate that BMSCs derived exosomal miR-221 is a key regulator of diabetic osteoporosis, which may represent a potential therapeutic target for diabetes-related skeletal disorders.